Penghakiman bagi Perusak Bumi: Tinjauan Teologi Ekologis dalam Wahyu 11:18 dan Implikasinya bagi Pendidikan Kristen Anak di Gereja - Darmadi, Daud (Sekolah Tinggi Teologi Tawangmangu, 2025)
The escalating degradation of the earth demands early environmental stewardship, which should be instilled through Christian education for children. However, church-based Christian education curricula often lack integrated content on environmental sustainability. The decreasing engagement of children with nature contributes to a generation less concerned with the care of creation. This study aims to explore the concept of ecological theology based on Revelation 11:18 and examine its relevance to children’s Christian education. The research employs a hermeneutical approach to the biblical text and a qualitative descriptive analysis of educational practices within the church. The findings reveal three key insights. First, Revelation 11:18 highlights a sharp contrast between those who faithfully fulfill God's mandate and those who destroy the earth; in the final judgment, God rewards those who care for the earth and punishes its destroyers. Second, environmental stewardship is an expression of faithful obedience and a reflection of human nature as the imago Dei, participating in the restoration of creation. Third, children’s Christian education plays a strategic role in shaping ecological awareness through faith-based curricula and sustainable environmental projects. This study concludes that integrating ecological theological values into children’s Christian education is essential. Churches must develop curricula that instill responsibility to care for and restore creation in accordance with God’s will. Abstrak Kerusakan bumi yang semakin masif menuntut upaya pelestarian lingkungan yang ditanamkan sejak dini melalui pendidikan Kristen anak. Namun, kurikulum pendidikan Kristen di gereja masih kurang mengintegrasikan materi mengenai kelestarian lingkungan. Aktivitas anak yang semakin minim di alam turut membentuk generasi yang kurang peduli terhadap keberlanjutan ciptaan. Penelitian ini bertujuan menggali konsep teologi ekologis berdasarkan Wahyu 11:18 dan mengkaji relevansinya bagi pendidikan Kristen anak. Metode yang digunakan adalah hermeneutik terhadap teks Alkitab serta analisis deskriptif kualitatif terhadap praktik pendidikan anak di gereja. Hasil penelitian menunjukkan: pertama, Wahyu 11:18 menegaskan kontras antara mereka yang setia menjalankan mandat Allah dan yang merusak bumi; Allah memberikan upah kepada yang memelihara bumi dan menghukum perusaknya pada hari penghakiman. Kedua, pemeliharaan lingkungan merupakan wujud kesetiaan iman dan refleksi natur manusia sebagai gambar Allah yang turut serta dalam pemulihan ciptaan. Ketiga, pendidikan Kristen anak berperan strategis dalam membentuk kesadaran ekologis melalui kurikulum berbasis iman dan proyek lingkungan berkelanjutan. Simpulan penelitian ini menegaskan pentingnya integrasi nilai-nilai teologi ekologis dalam pendidikan Kristen anak. Gereja perlu menyusun kurikulum yang menanamkan tanggung jawab untuk menjaga dan memulihkan ciptaan sesuai kehendak Allah.